Surgical Techniques for Haemodialysis Access-Induced Distal Ischaemia. Issue 1 (January 2016) - Al Shakarchi, Julien; Stolba, Jan; Houston, J. Graeme; Inston, Nicholas
Purpose: Haemodialysis access-induced distal ischaemia (HAIDI) is a significant complication of vascular access creation, and has traditionally been difficult to manage without loss of access. Current treatment options include ligation, banding, distal revascularisation with interval ligation (DRIL), proximalisation of the arterial inflow (PAI) and revision using distal flow (RUDI). The purpose of this review was to evaluate the effectiveness of the different surgical techniques in the treatment of HAIDI. Methods: Electronic databases were searched for studies assessing surgical techniques in the treatment of HAIDI in accordance with PRISMA. The primary outcome for the study was symptomatic relief for each technique, defined within each study. Secondary outcomes included comparison of early thrombosis rates following each different procedure. Results: Following strict inclusion/exclusion criteria by two reviewers, twenty-seven studies of surgical interventions were included and divided into subgroups for banding, DRIL, PAI and RUDI procedures. Both DRIL and banding procedures were found to have high rates of symptomatic relief. In addition, the DRIL has a significantly lower rate of early thrombosis than banding although the more recent papers seem to suggest that early thrombosis is less of a problem in banding. PAI and RUDI showed some promise but there were too few studies to be able to make any clear conclusions. Conclusions: All four procedures have high success rate in relieving ischaemic symptoms with the DRIL procedure having a significantly better vascular access patency rate than other techniques, although further well designed studies are required to compare all four surgical techniques.